An update on the age of national-level American swimmers. Manuscript and coaching applications - Stager, J.; Cornett, A.; Tanner, D.; Slaughter, E (Journal of Swimming Research, 2017)
The age of national-level American female swimmers increased from 1972 to 1996. Whether or not this trend has continued and whether or not a similar trend exists for male swimmers is unclear. PURPOSE: To analyze participant age for national-level female and male American swimmers from 1969 to 2016. METHODS: We calculated the mean age of all participants (ALL ENTRANTS) and athletes qualifying for championship heats (FINALISTS) at U.S. Long Course Swimming National Championships from 1969 to 2016. Three-way ANOVA was used to determine if ALL ENTRANTS, FINALISTS, and the difference between them (DIFFERENCE) differed by sex and varied within and across Olympiads. RESULTS: Significant sex by Olympiad interactions (P < 0.05) showed greater increases in age for women than for men. ALL ENTRANTS increased from 15.77 (95% CI, 14.74 to 16.80) to 19.28 years (95% CI, 19.13 to 19.43) for women and from 18.28 (95% CI, 17.40 to 19.16) to 20.28 years (95% CI, 20.08 to 20.48) for men. FINALISTS increased from 16.63 (95% CI, 16.25 to 17.01) to 20.63 years (95% CI, 19.22 to 22.04) for women and 18.80 (95% CI, 17.95 to 19.65) to 22.15 years (95% CI, 21.13 to 23.17) for men. DIFFERENCE increased from 0.67 years (95% CI, -0.03 to 0.43) to 1.36 years (95% CI, 0.90 to 1.82). CONCLUSION: The national-level American swim population has gotten older since 1969 to the extent that this group is now, from the perspective of age, distinct from the identically defined group from nearly five decades ago.